2006
DOI: 10.1016/j.bbadis.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone modulates cognition and amyloid-β deposition in Alzheimer APP transgenic mice

Abstract: Until recently, the study of hormonal influences in Alzheimer disease was limited to the role of sex steroids. Despite numerous epidemiological studies supporting a protective role for estrogen in Alzheimer disease, recent studies show that estrogen administration in elderly women increases the risk of disease. Reconciling these contradictory reports, we previously hypothesized that other hormones of the hypothalamic-pituitary-gonadal axis, such as luteinizing hormone, may be involved in the onset and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 54 publications
9
116
0
Order By: Relevance
“…Further, LH ablation for 3 mo. in an AD mouse model improved cognitive ability indicated through sustained spontaneous alternation behavior in a Y-maze task (Casadesus et al, 2006). Together with the present experiments, these studies implicate LH in mediating hippocampally-dependent memory function in both mice and rats.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Further, LH ablation for 3 mo. in an AD mouse model improved cognitive ability indicated through sustained spontaneous alternation behavior in a Y-maze task (Casadesus et al, 2006). Together with the present experiments, these studies implicate LH in mediating hippocampally-dependent memory function in both mice and rats.…”
Section: Discussionsupporting
confidence: 77%
“…A series of studies have shown that levels of soluble Aβ correlate with the degree of cognitive impairment and disease progression in animal models and AD subjects (Kuo et al, 1996;McLean et al, 1999;Mucke et al, 2000;Naslund et al, 2000) whereas increasing evidence has suggested that soluble non-fibrillar Aβ rather than the insoluble fibrillar counterpart is important for the pathophysiology of the disease (Walsh 1999;Lambert et al, 2000). In addition, LH has been found to cause elevated levels of Aβ in neuroblastoma cells in vitro (Bowen et al, 2004), and the prolonged suppression of LH in both normal mice (Bowen et al, 2004) and an AD mouse model (Casadesus et al, 2006) has been shown to decrease Aβ load and aggregates, respectively, in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the hypothalamicpituitary-gonadal (HPG) axis with aging has been postulated to drive aging-related diseases via alterations in cell signaling throughout the body Vadakkadath Meethal and Atwood, 2005). This altered cell cycle signaling, resulting from the decline in sex steroid and inhibin production and elevation in gonadotropin-releasing hormone, gonadotropin, and activin signaling, has been shown to drive postreproductive degenerative mechanisms involved in Alzheimer's disease Casadesus et al, 2006), osteoporosis (Sun et al, 2006), and blood-brain barrier integrity and associated diseases such as stroke (Wilson et al, 2008).…”
Section: Genetic and Age-linked Alterations In Lactate Homeostasis Unmentioning
confidence: 99%
“…21 This behavioral task, used to test working memory, is based on spontaneous alternation behavior, which describes the innate tendency of mice to visit arms that were not previously explored. All animals were allowed a 5-minute free run in the maze before testing to familiarize them with the apparatus and to foster alternation behavior.…”
Section: Behavioral Analysismentioning
confidence: 99%